A grade point average assessment of analytical and numerical methods for parameter extraction of a practical PV device. (May 2021) - Adeel, Muhammad; Hassan, Ahmad Kamal; Sher, Hadeed Ahmed; Murtaza, Ali Faisal
Abstract: This paper presents a comprehensive evaluation and ranking mechanism of analytical and meta-heuristic algorithms for the extraction of parameters of a practical PV device. A total of 10 algorithms are analyzed on single and two diode PV device models to extract the series and shunt resistances R s and R s h, respectively. As a benchmark, the commercially available Mono-Crystalline Sanyo-HIT215 and Multi-Crystalline Kyocera-KC200GT PV module were selected. The resulting parameters have been characterized under different values of temperature and irradiance. The I–V curves obtained using these algorithms are retrofitted on the I–V curves provided by the manufacturer. The evaluation is further enhanced by calculating the total error, fitness value, convergence time, and standard deviation in terms of error and time. Furthermore, a cumulative grade point average mechanism is introduced to rank the studied algorithms. Highlights: PV parameter extraction problem is addressed. 10 most widely used methods are compared. These methods are graded by assigning them grade point average values. Extensive simulations have been performed to assess the grading mechanism. Meta heuristics and Analytical methods are applied to one diode and two diode PV model.